The Cone Flare Crush Modified-T (CFCT) stenting technique for coronary artery bifurcation lesions. (October 2020) - Peverill, William T.; Incani, Alexander; Worthley, Stephen G.; Singbal, Yash; Garrahy, Paul J.; McCann, Andrew B.; Cox, Stephen V.; Moore, Peter T.; Lim, Richard Y.Y.; Fetahovic, Taufik; Connors, Gerard W.; Hall, Cindy; et al.
Abstract: Background: The present study is a prospective observational single arm clinical investigation, with parallel bench test interrogation, aimed at investigating the technical feasibility, safety and clinical outcomes with the cone flare crush modified-T (CFCT) bifurcation stenting technique. Bifurcation percutaneous coronary intervention (PCI) remains an area of ongoing procedural evolution. More widely applicable and reproducible techniques are required. Methods: From April 2018 until March 2019, 20 consecutive patients underwent bifurcation PCI using the CFCT technique with a Pt-Cr everolimus drug-eluting stent with a bioresorbable polymer. Exercise stress echocardiography was performed at 12-month follow-up. The primary outcome was a composite of cardiac related mortality, myocardial infarction, target lesion/vessel revascularization and stroke. Safety secondary endpoints included bleeding, all-cause mortality and stent thrombosis. Results: All patients underwent a successful CFCT bifurcation procedure with no complications to 30-day follow-up. One patient met the primary endpoint requiring target lesion revascularization at 9 months for stable angina. There were no other primary or secondary outcome events in the cohort. There were no strokes, deaths, stent thrombosis or myocardial infarction during the follow-up period. The mean CCS score improved from 2.25 to 0.25 (p < 0.0001). Optical coherence tomography (OCT) and bench test findings indicated optimal side branch ostial coverage and minimal redundant strut material crowding the neo-carina. Conclusions: The CFCT technique appears to be a safe, efficacious and feasible strategy for managing coronary artery bifurcation disease. Expanded and randomized datasets with longer term follow-up are required to further explore confirm this feasibility data. (ANZCTR ID: ACTRN12618001145291).